Validation of a coupled 3D CFD simulation model for an oxy-fuel cross-fired glass melting furnace with electric boosting. (August 2021) - Raič, Juraj; Gaber, Christian; Wachter, Philipp; Demuth, Martin; Gerhardter, Hannes; Knoll, Mario; Prieler, René; Hochenauer, Christoph
Highlights: Alternative combustion model for oxy-fuel combustion is scrutinized. Advanced iterative coupled method for stronger solution damping is introduced. Temperatures in the furnace were predicted within 4% of the experimental data. The energy exploitation of the furnace at a normalized cullet content of 50% was 34.5%. Abstract: Glass furnaces represent a continuous challenge for CFD simulations, which is attributed to the complex description of multiple phases: the turbulent gas phase, raw materials from a solid glass batch and the laminar liquid phase of the glass melt. Prevalence of unsuitable oxy-fuel combustion models, like the eddy-dissipation model, and the lack of advanced coupling methods for the coupling of combustion chamber and glass tank domains have been identified as research gaps in glass furnace simulations. These are tackled in a 3D CFD simulation model for an oxy-fuel glass furnace with electric boosting by introducing two significant improvements compared to previous approaches: (1) The partially-premixed steady diffusion flamelet model in combination with a skeletal25 reaction mechanism was used for combustion modelling. (2) An advanced iterative coupled simulation method is presented, which introduces damping of the solution and a rigorous termination condition. By employing the presented models, the respective temperatures in the combustion chamber and the glass tank were predicted within less than 1.93 % and 3.81 % of the experimental data.